2012
DOI: 10.1111/all.12057
|View full text |Cite
|
Sign up to set email alerts
|

Lipids are required for the development of Brazil nut allergy: the role of mouse and human iNKT cells

Abstract: Lipid fraction C from Brazil nut presents an essential adjuvant activity to Ber e 1 sensitization, and iNKT cells play a critical role in the development of Brazil nut-allergic response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 37 publications
3
69
0
Order By: Relevance
“…Lipids from the pollen coat are codelivered with the allergens and can modulate the immune responses of predisposed subjects by interacting with the innate immune system and iiNKT cells, and they can potentially induce NKT cell-dependent allergy disease and asthma [7,11,12]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lipids from the pollen coat are codelivered with the allergens and can modulate the immune responses of predisposed subjects by interacting with the innate immune system and iiNKT cells, and they can potentially induce NKT cell-dependent allergy disease and asthma [7,11,12]. …”
Section: Discussionmentioning
confidence: 99%
“…For example, an increased frequency of bee and wasp venom responsive to CD1a-restricted T cells in allergic individuals was recently described [31]. Furthermore, endogenous lipids from Brazil nut can act as adjuvants for the immune response against Ber e 1 allergen and iNKT cells play a crucial role in this response [12]. …”
Section: Discussionmentioning
confidence: 99%
“…64 However, it should be noted that some preliminary data suggest that plants and their pollen might contain iNKT cell antigens as well. [83][84][85] Altogether, recent findings indicate that antigens for iNKT cells are almost ubiquitous indoors and in the environment. As they will reach the airways with the inhaled air, it seems likely that iNKT cell antigens are present under normal conditions in the lung at low levels and could under certain conditions contribute to airway inflammation.…”
Section: Inkt Cells and The Microbiota In The Respiratory Tractmentioning
confidence: 99%
“…are not iNKT cells (Exley et al 2008;Montoya et al 2007), it is unclear at this time whether iNKT cells can respond to pollen derived lipids. Another study implicated recognition of plant lipids by iNKT cells (Mirotti et al 2013), but this recognition was not formally demonstrated.…”
Section: Further Aspects Of Environmental Inkt Cell Antigensmentioning
confidence: 99%